MetaSocieties in Metaverse: MetaEconomics and MetaManagement for MetaEnterprises and MetaCities - Wang, Fei-Yue; Qin, Rui; Wang, Xiao; Hu, Bin (IEEE transactions on computational social systems, 2022)
Welcome to the first issue of the IEEE Transactions on Computational Social Systems (TCSS) of 2022. We would like to take this opportunity to express our sincere thanks to our associate editors, reviewers, authors, and readers for your great support and effort devoted to IEEE TCSS. Happy New Year to you all, and cheers to health, happiness, and high-producing in 2022!